Simplified heat generation model for lithium ion battery used in electric vehicle - Ismail , Nur Hazima Faezaa; Toha, Siti Fauziah; Mohd Azubir, Nor Aziah; Md Ishak, Nizam Hanis; Hassan, Mohd Khair; Ibrahim, Babul Salam Ksm (IOP Publishing, 2013)
It is known that temperature variations inside a battery may greatly affect its performance, life, and reliability. In an effort to gain a better understanding of the heat generation in Lithium ion batteries, a simple heat generation models were constructed in order to predict the thermal behaviour of a battery pack. The Lithium ion battery presents in this paper is Lithium Iron Phosphate (LiFePO4). The results show that the model can be viewed as an acceptable approximation for the variation of the battery pack temperature at a continuous discharge current from data provided by the manufacturer and literature.